THE RATE OF CARDIAC RHYTHM RECOVERY POST EXERTION IN PHYSICAL REHABILITATION OF CARDIOLOGICAL PATIENTS - O. А. Ivanova; S. G. Kuklin (Кардиоваскулярная терапия и профилактика, 2018)
Taken the rising mortality and morbidity of the population due to cardiovascular diseases (CVD), rehabilitation of cardiovascular patients remains actual. Regular exercises are the leading components of cardiorehabilitation, that is evidently beneficial. Taken this, the question raises on the adequacy and efficacy of training regimens. Utilization of the parameter representing the velocity of heart rate decline by every minute of recovery phase after the exertion, is quite informative. The borderline set for heart rate, with increasing cardiovascular risk if below. Dynamics of such parameter during the programs of physical rehabilitation might be a marker of the events efficacy. Recently, there is a deficiency of information on the normal parameters of heart rate recovery rate in CVD patients. Hence a question raises, on the unification of approaches in evaluation of recovery period and data collection on the influence of long term exercises on CVD prognosis.